Path Planning on Jetson Platform for a Differential Robot - Gastélum Zazueta, Osiel; Chávez Borrego, William Arad; Magdaleno López, Camila; Orozco Rosas, Ulises; Picos, Kenia (My University, 2025)
This work presents the development and implementation of an autonomous navigation system for the TurtleBot 2 robot, leveraging the ROS (Robot Operating System) framework. The system integrates a discrete path-planning algorithm to achieve an efficient and adaptive trajectory. The proposed approach utilizes the A* algorithm for path planning. The TurtleBot 2 is a widely recognized mobile robot platform designed for research and education in robotics. At the same time, the Jetson TX2 is a compact, high-performance computing board that facilitates real-time processing and AI integration. The results validate the proposed system's performance, highlighting the robot's ability to follow predefined paths, maintain accurate positioning, and reach goals efficiently. This work demonstrates the feasibility of integrating discrete path planning techniques with robotics frameworks, providing valuable insights into autonomous navigation challenges and solutions in robotics research and development.
Revista Aristas Ciencia Básica y aplicada
Keywords: Autonomous Navigation; Robot Operating System; Jetson TX2; Path Planning; Mobile Robots; Campus Tijuana